Congenital Anaplastic Rhabdomyosarcoma Presenting As Abdominal Wall Mass - Mondal, Krishnendu (Iran J Pathol, 2016)
Rhabdomyosarcoma encompasses a group of malignant myogenic neoplasms expressing a multitude of clinical and pathological diversities. It is the commonest soft tissue sarcoma of childhood but neonates are rarely affected. Embryonal subtype is the most frequent. Head-neck and genitourinary tracts are predominant sites, while trunk is considered among the unusual sites of rhabdomyosarcoma. Herein we report a case of anaplastic rhabdomyosarcoma in a newborn girl presenting, at the Pediatric Surgery Outpatient Department of North Bengal Medical College and Hospital, India in 2013 with a large tumor mass in the left flank region, arising from abdominal wall muscles.